2020
DOI: 10.3390/su12041302
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Second Foreign Language Proficiency: The Mediating Role of Foreign Language Enjoyment

Abstract: Inadequate research attention has been paid to the learning of a third language. For this reason, this study explores senior English major students' learning of additional foreign languages in seven universities in Shaanxi Province, China. The study examines the relationship between the participants' motivation and language proficiency through a questionnaire, and the collected data are analyzed using hierarchical linear regression analysis. The results identify that the participants' instrumental and integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 52 publications
14
75
1
2
Order By: Relevance
“…Using a comparable cross-sectional design and focusing on students' second FL, Zhang et al (2020) found that their 335 Chinese university students' instrumental and integrative motivation positively influenced their second FL self-rated proficiency (mostly Japanese, French and German). Further analysis revealed that the relationship between motivation and self-rated FL proficiency was mediated by FLE.…”
Section: The Role Of Emotions and Motivation On Fl Performancementioning
confidence: 99%
“…Using a comparable cross-sectional design and focusing on students' second FL, Zhang et al (2020) found that their 335 Chinese university students' instrumental and integrative motivation positively influenced their second FL self-rated proficiency (mostly Japanese, French and German). Further analysis revealed that the relationship between motivation and self-rated FL proficiency was mediated by FLE.…”
Section: The Role Of Emotions and Motivation On Fl Performancementioning
confidence: 99%
“…High FLE learners usually keep good relationships with teachers and may try to be considerate to decrease teachers' workload by engaging in self-correction. Moreover, the finding that error code was rated higher by high FLE learners than low FLE learners at the lower proficiency level could be explained by the mediating effects of FLE on learner-related variables such as proficiency (Zhang et al, 2020). In other words, just like upper intermediate learners, learners with lower level of proficiency also preferred less explicit WCF types when they scored high on FLE scales.…”
Section: Discussionmentioning
confidence: 96%
“…FLE has also been demonstrated to be a strong predictor of learners' willingness to communicate , learners' performances on lexical decision tasks (Dewaele and Alfawzan, 2018) and L2 achievement (Jin and Zhang, 2018). Moreover, FLE is found to have a mediating role in the relationships between learners' motivation and language proficiency (Zhang et al, 2020). Taken together, FLE is most likely to be triggered by teacher-related factors, boosts learners' capacity in FL, affects the process of the target language, and mediates other affective factors such as motivation as well as learners' proficiency level.…”
Section: Effect Of Error Type On Written Corrective Feedbackmentioning
confidence: 94%
“…While these studies identify the influence of either motivation, Wallace, and Leong (2020) found that EFL Chinese students demonstrate high instrumental as well as integrative motivation for learning English. Similarly, Zhang, Dai and Wang (2020) also found that proficiency in English of the English major university students in China is constrained by their integrative and instrumental motivations. Above all, the findings of these studies suggest that whatever its type or nature, motivation is found to have a crucial role in learning English as an L2.…”
Section: Literature Reviewmentioning
confidence: 90%